Homerinis himnas Demetrai: mito alegorija ir žanro tradicija - Kudulytė-Kairienė, Audronė (Literatūra, 2008)
The article deals with the Homeric hymn to Demeter, composed in the late seventh century B. C. This hymn tells how Hades, lord of the Underworld, abducted the goddess Persephone and how her mother, Demeter, the goddess of vegetation and fruitfulness, forced Zeus to allow her daughter to return to the earth for a part of each year. The myth about the rape of Persephone can be interpreted as an allegory for ancient Greek marriage. The Greeks felt that marriage was a sort of abduction of the bride by the groom from the bride’s family. After marriage girls accepted their new role in society and did not return to their mothers. The hymn was written from a feminine point of view. The creative potential of female wrath is emphasized in the poem. Some scholars argue that the hymn to Demeter derived from a female oral tradition and that it could be composed by a woman. The analysis of the hymn made in the recent article contradicts this suggestion as it reveals that some patterns and scenes could be borrowed from the epic tradition. The type scenes in the hymn are used in much the same way that they are used in the Iliad and Odyssey.